Hypertensive disorders of pregnancy and risk of asthma and chronic obstructive pulmonary disease: a prospective cohort studyResearch in context - Yi-Xin Wang; Raphaëlle Varraso; Orianne Dumas; Jennifer J. Stuart; Andrea Florio; Liang Wang; Janet W. Rich-Edwards; Carlos A. Camargo, Jr; Jorge E. Chavarro (Elsevier, 2023)
Summary: Background: Hypertensive disorders of pregnancy (HDPs) have been associated with respiratory dysfunction during pregnancy and postpartum. In this study, we explored the associations between HDPs (gestational hypertension and preeclampsia) and the risk of incident asthma and chronic obstructive pulmonary disease (COPD) during adulthood and the potential mediating role of chronic hypertension. Methods: We included parous nurses in the Nurses' Health Study II reporting a pregnancy lasting no less than 6 months. The associations between HDPs and asthma and COPD were estimated using Cox proportional hazards models with adjustment for confounders. Findings: We included 73,807 nurses [92.5% (68,246 of 73,807) White] in asthma analyses and 79,843 [92.4% (73,746 of 79,843) White] in COPD analyses, whose mean (SD, range) age, at baseline, were both 34.8 (4.7, 25.0-44.0) years. During 24 years of follow-up, we identified 2663 incident cases of asthma and 537 COPD. Compared with nurses without HDPs, nurses reporting HDPs had an increased HR for incident asthma and COPD of 1.22 (95% CI 1.10-1.36) and 1.39 (95% CI 1.11-1.74), respectively. The risk of asthma was similar when gestational hypertension and preeclampsia were assessed separately [HR = 1.25 (95% CI 1.08-1.43) and 1.24 (95% CI 1.11-1.38), respectively]. However, only nurses with preeclampsia had a higher risk of COPD (HR = 1.41, 95% CI 1.11-1.78). Mediation analyses estimated that chronic hypertension explained 18.6% (95% CI 8.9-35.0%) and 10.7% (95% CI 2.9-32.4%) of the associations between HDPs and asthma and COPD, respectively. Interpretation: HDPs may serve as useful markers of increased susceptibility to chronic respiratory diseases during adulthood. Funding: The National Institutes of Health grants.